2019
DOI: 10.1080/21501203.2019.1707315
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Bax and Bcl-2 genes by secondary metabolites produced byPenicillium rubensJGIPR9 causes the apoptosis of cancer cell lines

Abstract: Search for an efficient anti-cancer compound of natural origin with well-defined mechanisms of action is an important scientific pursuit today, due to cancer being the second leading cause for the death of affected people. The members of the genus Penicillium are one of the important sources of bioactive compounds. In the present study, Penicillium rubens, isolated from a garden soil in Madurai district of Tamil Nadu, was found to produce a highly promising anti-cancer metabolite. The percentage viabilities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In the present context, AK-7 extract significantly induced and influenced the apoptosis mechanism in the PA-1 cell line through a series of mechanisms that finally led to mitochondrial dysfunction and cell death compared to the untreated cell line. Venkatachalam et al (2019) observed increased apoptosis in HepG2, HeLa, and MCF-7 cancer cell lines treated with Penicillium rubens extract; they also observed upregulation of Bcl-2, Bax, and p53 expressions levels significantly increased the apoptotic efficacy [61]. It was evident from the literature that induced cancer cell death is the result of potential metabolites present in the extracts.…”
Section: Discussionmentioning
confidence: 91%
“…In the present context, AK-7 extract significantly induced and influenced the apoptosis mechanism in the PA-1 cell line through a series of mechanisms that finally led to mitochondrial dysfunction and cell death compared to the untreated cell line. Venkatachalam et al (2019) observed increased apoptosis in HepG2, HeLa, and MCF-7 cancer cell lines treated with Penicillium rubens extract; they also observed upregulation of Bcl-2, Bax, and p53 expressions levels significantly increased the apoptotic efficacy [61]. It was evident from the literature that induced cancer cell death is the result of potential metabolites present in the extracts.…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported that Candida contains a variety of human commensal species, such as Candida albicans , which can alleviate the intestinal mucosal damage caused by dextran sulfate-induced colitis in mice, exhibit immunomodulatory properties, and maintain intestinal homeostasis [ 50 ]. Penicillium has been reported to produce multiple secondary metabolites that inhibit tumor cell growth [ 51 ]. Aspergillus produces aflatoxins, which can cause opportunistic infections and liver damage in humans [ 52 ], and recent studies have shown that its abundance is increased in the gut of patients with multiple sclerosis [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fungal isolate with promising anti-cancer properties was identified as Penicillium rubens by 18s rRNA sequencing (Biokart India Pvt. Ltd., Bengaluru) 10 . The sequence was submitted to Genbank and the accession number obtained was MH816935 (Penicillium rubens JGIPR9).…”
Section: Results: Identification Of the Promising Isolatementioning
confidence: 99%
“…A list of different nutrients used in the single factor system along with the basal media for biomass production (response 1) and concentration of bioactive metabolite (response 2) are listed in Table 1. Culture conditions such as incubation period (day 9-14), pH (3)(4)(5)(6)(7)(8)(9)(10)(11) and temperature (4 °C, RT [24-28 °C], 40 °C and 60 °C) were also considered for enhancing biomass production and quantity of bioactive metabolite. The extraction of metabolite and determination of biomass weight were performed as previously mentioned.…”
Section: Effect Of Varying Culture Conditionsmentioning
confidence: 99%